9(q+2)-3(q+3)=9

Simple and best practice solution for 9(q+2)-3(q+3)=9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9(q+2)-3(q+3)=9 equation:


Simplifying
9(q + 2) + -3(q + 3) = 9

Reorder the terms:
9(2 + q) + -3(q + 3) = 9
(2 * 9 + q * 9) + -3(q + 3) = 9
(18 + 9q) + -3(q + 3) = 9

Reorder the terms:
18 + 9q + -3(3 + q) = 9
18 + 9q + (3 * -3 + q * -3) = 9
18 + 9q + (-9 + -3q) = 9

Reorder the terms:
18 + -9 + 9q + -3q = 9

Combine like terms: 18 + -9 = 9
9 + 9q + -3q = 9

Combine like terms: 9q + -3q = 6q
9 + 6q = 9

Add '-9' to each side of the equation.
9 + -9 + 6q = 9 + -9

Combine like terms: 9 + -9 = 0
0 + 6q = 9 + -9
6q = 9 + -9

Combine like terms: 9 + -9 = 0
6q = 0

Solving
6q = 0

Solving for variable 'q'.

Move all terms containing q to the left, all other terms to the right.

Divide each side by '6'.
q = 0

Simplifying
q = 0

See similar equations:

| x-105=6x | | .33x+7=1 | | -18-8x=-10(x+4) | | f(x)=15x^4+8x^3-18x^2+1 | | m-1=-13+3m | | 3/103/4 | | 3(2x-5)+24-4x=9 | | 25x^2=-45x-18 | | 2/3(x-9)^-(1/3) | | -10-3a=a-6-3a | | x+x+55(x+38)=180 | | 25x^2+45x-18=0 | | 45=9-2b | | 4-4a=-3a+a | | 3k-2=4 | | .25x+3=-9 | | x=4x-0.1x^2 | | 11ln(9x)=12 | | 7+8r=7-4r | | x+x+43*x-32=180 | | 3(a-10)=42 | | -.5x+15=20 | | -2+5x=-3x+7x | | p+.12p=56 | | -5=a^2+3 | | t/3+t/2-350=270 | | 1-4v=15-6v | | 11+x=-33 | | http://media.apexlearning.com/Images/201305/30/25030d05-eb1d-46a7-bf10-8e6086df63c3.gif | | -12/6=X | | p+.12p=52 | | 5n+4n=8n-7 |

Equations solver categories